Mesozooplankton community in near-hypoxic and hypoxic layers of the Persian Gulf and the Gulf of Oman. (November 2022) - Abedi, Ehsan; Seyfabadi, Jafar; Saleh, Abolfazl; Sari, Alireza
Abstract: To assess the role of near-hypoxic and hypoxic conditions on the mesozooplankton community, we studied twenty stations in the Persian Gulf and the Gulf of Oman. The physicochemical parameters were measured using a CTD probe and mesozooplankton were sampled vertically using a closing net. Results showed the hypoxic conditions of 0.52 ± 0.11, 1.40 ± 0.48, and 0.84 ± 0.08 in the lower layers in stations T11S3, T0S8B, and T9S5 in the Gulf of Oman and near-hypoxic conditions in station T6S3 (2.99 ± 0.05) in the Persian Gulf. The marginal test revealed that stratification during summer and dissolved oxygen and salinity during spring in the Persian Gulf and temperature, stratification, and dissolved oxygen during spring in the Gulf of Oman significantly explained the variation of mesozooplankton composition in the study areas ( p < 0.05). The present study reveals some general patterns of mesozooplankton assemblage in near-hypoxic and hypoxic conditions, but a future detailed investigation will be essential. Highlights: Near-hypoxia in the Persian Gulf and hypoxia in the Gulf of Oman and related mesozooplankton were evaluated. Near-hypoxic and hypoxic conditions occurred at 100-200 m layers of the Persian Gulf and the Gulf of Oman. The negative effect of hypoxia on total mesozooplankton abundances stations in the Gulf of Oman was observed. The mesozooplankton abundances in the lower layer compared to the upper layer of stations with near-hypoxic and hypoxic conditions in the Persian Gulf and the Gulf of Oman decreased.